Pengaruh Profesionalisme, Independensi, Pengetahuan Mendeteksi kekeliruan, Pengalaman dan Etika Profesi Auditor Terhadap Pertimbangan Tingkat Materialitas pada Kap di Wilayah bali - Ni Putu Yuni Astari; Ni Putu Riasning; Made Putra Manuaba (Jurnal Riset Akuntansi Warmadewa, 2020)
Consideration of the level of materiality is very important in making decisions, this is related to the final results of the audit that will be used by users of the information, so it must be carried out with great care and care. The purpose of determining materiality is to help the auditor plan the collection of sufficient evidence. This study aims to analyze the influence of professionalism, independence, knowledge of error detection, experience and professional ethics due to materiality level considerations in the public accountant office (KAP) in Bali. The sample used in this study were 79 auditors who work at public accounting firms (KAP) in the Bali region. The dependent variable in this study is a consideration of the level of materiality and the independent variables in this study are professionalism, independence, knowledge of error detection, experience, and professional ethics. The research method used is a quantitative method with primary data obtained using a questionnaire. The data analysis technique used in this study used double-line analysis with the sampling method using nonprobability sampling method with saturated sampling technique or census. This research data is in the form of a questionnaire which is then processed using the Statistica Program and Service Solution (SPSS) program. The results of this study indicate that the variables of professionalism, independence, knowledge of error detection, experience and professional ethics have a significant positive effect on consideration of the level of materiality.